3D model reconstruction of human knee joint based on medical images for education purpose - Choy, Chee Mun (2021)
The medical images are the fundamental equipment that will help the medical students or even specialists on finding the problems and diseases in the body. The objective of this project is to develop 3D reconstructed anatomy structure based on real medical images of the patient to allow students to study the 3D anatomy structure from actual medical images. Segmentation techniques are the methods which helps on detecting the anomalies or the diseases inside the bodies. The 3D slicer workbench is a software which provides different type of the modules and systems that will help to generate a 3D models of the anatomy and the problems from the medical images. Along with the workbench, a new module can be created to help on solving the problems as well as easing the studies for the medical students. Image segmentations consist of few methods that can be used to do the image processing onto the DICOM image so that to create a 3D model according to it, but proper method must be chosen wisely. Moreover, the 3D slicer workbench project template had provided basic 3D slicer modules and can be used to create a new model for the project. The model was done so by using some segmentation techniques and smoothing techniques. Once the process was done, the 3D model visualization can be seen. The 3D model was then printed out with the software called Snapmaker Luban along with the 3D printing machine. During the project, the waterfall development method was used.